Functional neuroanatomy of mania - Cotovio, Gonçalo (2022)
Funding Information: GC is supported by Fundação para a Ciência e Tecnologia (FCT) through a PhD Scholarship (SFRH/BD/130210/2017). AJO-M is supported by grant FCT-PTDC/MEC-PSQ/ 30302/2017-IC&DT-LISBOA-01-0145-FEDER, funded by national funds from FCT/MCTES and co-funded by FEDER, under the Partnership Agreement Lisboa 2020—Programa Operacional Regional de Lisboa, and the BOUNCE (grant agreement number 777167) and FAITH (grant agreement number 875358) projects, funded by the European Union’s Horizon 2020 research and innovation programme. GC and AJO-M are supported by grant FCT-PTDC/MED-NEU/31331/2017, funded by FCT/MCTES. Funding Information: AJO-M was national coordinator for Portugal of a non-interventional study (EDMS-ERI-143085581, 4.0) to characterize a Treatment-Resistant Depression Cohort in Europe, sponsored by Janssen-Cilag, Ltd (2019-2020), is recipient of a grant from Schuhfried GmBH for norming and validation of cognitive tests, and is national coordinator for Portugal of trials of psilocybin therapy for treatment-resistant depression, sponsored by Compass Pathways, Ltd (EudraCT number 2017-003288-36 and 2020-001348-25), and of esketamine for treatment-resistant depression, sponsored by Janssen-Cilag, Ltd (EudraCT NUMBER: 2019-002992-33). None of the aforementioned agencies had a role in the design and conduct of the study, in the collection, management, analysis, and interpretation of the data, in the preparation, review, or approval of the manuscript, nor in the decision to submit the manuscript for publication. Publisher Copyright: © 2022, The Author(s).